2006
DOI: 10.1016/j.rapm.2005.10.008
|View full text |Cite
|
Sign up to set email alerts
|

The Bilateral Superficial Cervical Plexus Block With 0.75% Ropivacaine Administered Before or After Surgery Does Not Prevent Postoperative Pain After Total Thyroidectomy

Abstract: Bilateral superficial cervical plexus block with 0.75% ropivacaine administered before or after surgery does not improve postoperative analgesia after total thyroidectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
62
2
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(67 citation statements)
references
References 20 publications
2
62
2
1
Order By: Relevance
“…While in postoperative blocks surgery may change the landmarks and dissection may cause local anaesthetic to leak into other facial planes. Herbland et al comparing the presurgical with postsurgical block found the two to be comparable but contrarily not highly efficacious in postthyroidectomy pain control [12]. Messner et al advised the use of presurgical block keeping in mind its preemptive effect [13].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While in postoperative blocks surgery may change the landmarks and dissection may cause local anaesthetic to leak into other facial planes. Herbland et al comparing the presurgical with postsurgical block found the two to be comparable but contrarily not highly efficacious in postthyroidectomy pain control [12]. Messner et al advised the use of presurgical block keeping in mind its preemptive effect [13].…”
Section: Discussionmentioning
confidence: 99%
“…Addition of adrenaline can not only prolong the effect of the block but also reduce the peak plasma levels of local anaesthetics [10,12]. Clonidine is also known to enhance the efficacy and duration of the block [14] and has been found to decrease postoperative nausea and vomiting [15].…”
Section: Discussionmentioning
confidence: 99%
“…In our study, however, this alleged superiority of SCPB over GA was not confirmed, as the same number of patients requested analgesics. Herbland et al 9 reached a similar result when performing SCPB with ropivacaine 0.75%, before or after thyroidectomy in patients under GA; these authors found that the block did not reduce the need for postoperative analgesics.…”
Section: Discussionmentioning
confidence: 75%
“…Herbland et al (24) obtained similar results for patients who received and did not receive bilateral superficial cervical plexus block in total thyroidectomy operations in terms of their analgesic needs and postoperative pain scores (24). Similarly in our study which we conducted for postoperative analgesic purpose, only 15 out of 75 patients in the BSCPB group (20%) had postoperative opioid need, whereas this rate was found to be 64 out of 75 patients (85%) in the control group (in which block administration was not performed) (85%) (p<0.05) and again, when we compared opioid consumption, the tramadole consumption in the BSCPB group was found to be significantly lower than the control group (p<0.05).…”
Section: Discussionmentioning
confidence: 82%